From reflection to diffraction: exploring the use of vignettes within post-humanist and multi-species research. (December 2021) - Jenkins, Nicholas; Ritchie, Louise; Quinn, Sam
This article explores the use of vignettes in qualitative research from a post-humanist and multi-species perspective. Drawing on methodological principles espoused by Karen Barad and Donna Haraway, as well as empirical data from the Dementia Dog pilot project in Scotland, UK, we explore the use of vignettes as a technique for understanding human–dog relations in dementia. In so doing, we outline an approach to using vignettes that is guided by principles of diffraction, which is contrasted with humanist principles of interpretivism, reflection and representation. Moving away from humanist methodology, we argue, calls for new approaches to evaluating the quality of vignettes. This involves disrupting conventional approaches, within which vignettes are defined by their purpose and evaluated according to fixed criteria (e.g. validity, authenticity and trustworthiness) . In their place, we argue for an approach to evaluating vignettes that is rooted in performativity and guided by the question: What can a vignette do ?